Understanding multiplexity of collaborative emergency management networks - Kapucu, Naim; Hu, Qian (2016)
This article explores the multiplex relationships among organizations within the context of emergency management. It examines the role of friendship networks and disaster preparedness networks in predicting sustainable collaborative disaster response networks. Furthermore, it examines the impact of emergency management systems on network building and sustainability. This article applies inferential network analysis methods in analyzing relationships among emergency management networks and examines the predictive power of preestablished network arrangements. This research suggests that friendship networks are important for encouraging organizations to be involved in disaster preparedness networks. Yet it is the collaboration ties during disaster preparedness that influence the formation of collaborations during disaster response. Structural attributes of emergency management systems have impacts on the development of multiplex relationships among organizations within various networks. These findings not only contribute to developing sustainable emergency management networks but also provide insights for building collaborative networks in a broader context.
Keywords: Disaster prevention